Lipase-catalyzed reactions in organic and supercritical solvents : Application to fat-soluble vitamin determination in milk powder and infant formula - Turner, Charlotta; Persson, Mattias; Mathiasson, Lennart; Adlercreutz, Patrick; King, Jerry W. (Enzyme and Microbial Technology, 2001)
The aim of this study was to thoroughly investigate the possibility of using enzyme catalyzed hydrolysis and alcoholysis of ester bonds in vitamin A and E esters to facilitate their determination in different food formulas. Two vitamin esters, retinyl palmitate and α-tocopheryl acetate were used as model compounds and two food formulas, milk powder and infant formula, were used as model matrices. Six lipase preparations and one esterase preparation were investigated in the solvents di-isopropyl ether, hexane/ethanol and supercritical carbon dioxide containing ethanol. Three of the enzyme preparations, lipases from Candida antarctica (Novozyme 435), Rhizomucor miehei (Lipozyme IM) and Pseudomonas cepacia, showed considerably higher activity toward retinyl palmitate than the other four enzyme preparations. There was no observed activity with α-tocopheryl acetate using any of the enzyme preparations. Novozyme 435 showed highest activity in supercritical fluid and generally larger tolerance to variations of the investigated parameters. Using this enzyme preparation in supercritical carbon dioxide containing 3 vol% ethanol and 0.03 vol% water at 366 bar and 80°C, quantitative conversion of retinyl palmitate to retinol was obtained. These conditions were then used for simultaneous lipase-catalyzed reaction and extraction of vitamin A and E from milk powder and infant formula. The developed supercritical fluid extraction method using immobilized Candida antarctica preparation seems to be more beneficial to the oxidation prone vitamins A and E compared to extraction methodologies based on alkaline saponification, resulting in comparatively higher recoveries.